CEFR aligned corpus contrastive genre analysis of sales emails of entrepreneurship undergraduates - Nur Baiti, Ismail Shauki (2021)
This study investigates the generical features used in writing business discourse prepared by the undergraduates of Universiti Malaysia Kelantan (UMK). The aim of this research is to contrast the generic structure of student’s sales email and Bhatia’s (1993) sales promotional letter. Data is gathered from the student’s assignment for English for Business subject submitted online. The methodology used in this thesis of written communication is Computer-Assisted Corpus Analysis (CACA) by Singh (2014). The particular moves and lexical frequency in both texts; Sales Reply Email and Sales Inquiry Email were manually tagged and later, categorised individually. The moves found were then analysed by two interraters before their agreement were calculated using Cohen’s kappa method. Then, the lexical variation was programmed into CLAWS Tagger and AntConc applications. The rhetorical structure of Sales Reply Emails has 9 moves while Sales Inquiry Emails has 7 moves. Nevertheless, the lexical analysis which compared students’ writings to the global CEFR scale have shown that only 35 words of C1 CEFR level are utilised by the students. Based on the findings, despite the similarities in the moves applied by the students, there are also apparent dissimilarities in terms of the content and organisation of the moves utilized.